Reviver a mãe: sexo, cultura e outras criações - Padilha, Taoana Aymone (2024)
This work takes a journey through the works of Sigmund Freud, Karen Horney and Luce Irigaray, with the aim of problematizing the phallocentric view of sexuality. With the contributions of Horney and Irigaray, authors who challenged this view at different times and in different places around the world, the research focuses on feminist and feminine approaches, proposing new readings that take into account the specificities of the female sex and the place of the mother, both in the unconscious and in cultural constructions. In this sense, feminist epistemology becomes fundamental for questioning the production of traditional psychoanalytic knowledge, opening up space for the valorization of female genealogies, which have historically been neglected in this field. This study challenges the classic interpretations of psychoanalysis, but also sheds light on the female voices and legacies that, over time, have created new possibilities for thinking about subjectivities, sexualities and the relationship between human beings and the environment, from the perspective of biopsychosocial complexity